PEMANFAATAN RAMUAN TRADISIONAL KOMBINASI JAHE DAN BAWANG MERAH TERHADAP SKALA NYERI PADA PASIEN OSTEOARTRITIS DI DUSUN MATAH SINGODUTAN SELOGIRI - Handono, Nugroho Priyo (Akademi Keperawatan Giri Satria Husada Wonogiri, 2019)
Background: Osteoarthritis (OA) is a degenerative disease of bones characterized by loss of articular cartilage (joints). Joint pain is common in OA patients. Joint pain can be reduced pharmacologically and non pharmacologically. This study was to determine the effectiveness of the traditional herb combination of ginger and shallot on pain scales in OA patients.Objective: To compile a resume of medical surgical nursing care in DM patients to determine the effectiveness of the traditional combination of ginger and shallot on the pain scale in OA patients.Research Methods: This type of research uses qualitative research with a case study design. This research was conducted in Dusun Matah Singodutan Selogiri February 10, 2019. The population in this study were 10 OA patients in the Matah Singodutan Selogiri Hamlet, the sample in this study was taken using inclusion criteria and sample homogeneity of 3 people. The pain scale is measured using a numerical scale.Results: The results of the assessment of all respondents showed subjective results that the majority of respondents complained of experiencing joint pain in both knees with a pain scale of 7 - 8 which can be categorized as severe pain. After compressing ginger and shallot for 5 days with a frequency of action 2 times a day (morning and evening), the results of respondents I, II and III stated that the pain decreased and the pain scale decreased to 4, 3, 4 in the moderate and mild pain category.Conclusion: Ginger and shallot compresses can reduce joint pain in osteoarthritis sufferers. The suggestion for future research is to measure the level of inflammation in OA patients.